Institutionalizing social entrepreneurship in regulatory space: Reporting and disclosure by community interest companies - Nicholls, Alex (Accounting, organizations and society, 2010)
In 2005, the British parliament passed legislation to make available the first new legal form of incorporation in over a century: the Community Interest Company (CIC). This initiative represented an important element within a larger set of public policy measures that aimed to create a more enabling environment for the accelerated growth of social entrepreneurship and, specifically, social enterprises. In an exploratory study, this paper presents an analysis of the regulatory space within which the reporting and disclosure practices for CICs were negotiated. Three elements within the regulatory space are identified as having explanatory value: regulatory boundaries that set and limit the terms of negotiation around regulatory practice; the key actors that engage in a process of negotiation around the establishment of actual practice; the range of debate and conflicting ideas that inform regulatory negotiation and legitimating consensus. The analysis suggests that a normative logic of light touch regulation was of particular importance within the wider UK policy context from within which CICs emerged and that the CIC Regulator acts as a mediator of disclosure information across multiple user constituencies. Empirically, this paper draws upon a sample of 80 published CIC annual reports to consider two aspects of CIC reporting: the quantity of information provided and the type of data presented. These data demonstrate the limitations and challenges of current CIC regulatory disclosure practices for key users of reporting information, particularly in terms of perceptions of organizational legitimacy. Conclusions are drawn concerning these limitations, particularly in terms of their implications for public policy. In terms of new research, this paper makes two important contributions. First, it develops theory in terms of (social) reporting and public policy with respect to the regulatory mechanisms that relate the two. This has yet to be explored in social entrepreneurship research. Second, this paper includes a preliminary examination of the reporting practices of CICs in their policy context, including an analysis of a sample of the publicly available CIC annual reports that have been filed to date. This data set has yet to be the subject of any other academic research.